The analysis of events in Biblical narratives - D F Tolmie (Acta Theologica)
In this article the way in which events are analysed in narrative-critical approaches to Biblical narratives is discussed. In many of these analyses one can detect a tendency to reduce the analysis of events to a discussion of only one or two aspects. Although, as such, the results of an analysis of events based on such a view of events may be quite legitimate, it may result in important features being overlooked. In order to rectify this, it is proposed in this article that scholars who follow a narrative-critical approach to Biblical narratives should take note of the sophisticated models already developed within theory of literature for the analysis of events. Some of these models are discussed and then illustrated by means of two examples: Genesis 2:4b-3:25 and Acts 27:1-44.